Tinjauan Ancaman Wabah dan Penyakit Akibat Perubahan Iklim - Ray March Syahadat; Balqis Nailufar; Billy Aditya Pratama; Ismail Saleh; Isti Mulyawati (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2021)
Background: The increase of disease outbreaks that have emerged in the last decade raises the question of whether it is related to climate change? Objectives: This article attempts to provide answers through a literature review. Research Metodes: VOSviewer application was used to help select topics to be discussed. Twenty articles related to outbreak, diseases and climate change were selected and then presented descriptively. Findings: The results obtained by climate change contribute to imbalances that can lead to disasters including disease outbreaks. Therefore, humans should start placing themselves as part of the ecosystem, not the ruler of the ecosystem. Conclusion: A science and technology approach based on local values is needed, by utilizing good environmental communication to provide knowledge to the community so that they are able to adapt and be aware of preventive efforts to realize a healthy life.